2018
DOI: 10.2116/analsci.18p441
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Synephrine Enantiomers in Citrus Fruits by a Reversed Phase HPLC after Chiral Precolumn Derivatization

Abstract: Racemic synephrine, which was transformed into diastereomers by derivatization with 2,3,4,6-tetra-O-acetyl-β-Dglucopyranosil isothiocyanate, was resolved by a reversed phase HPLC with UV detection at 254 nm. The total contents of synephrine enantiomers in citrus fruit samples were exocarp > mesocarp > endocarp > sarcocarp, suggesting that synephrine content of outer side of citrus fruits was higher than that of the inner side. (R)-Synephrine was detected in exocarp of eleven fresh citrus fruits, except for lem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Although the content of synephrine did not change during drying, conversion between (R)synephrine and (S)-synephrine may occur at high temperatures. 33…”
Section: Hplc-pda Profile Of Seven Bioactive Components During Harvesting and Dryingmentioning
confidence: 99%
“…Although the content of synephrine did not change during drying, conversion between (R)synephrine and (S)-synephrine may occur at high temperatures. 33…”
Section: Hplc-pda Profile Of Seven Bioactive Components During Harvesting and Dryingmentioning
confidence: 99%
“…1,7 Synephrine is an enantiomeric compound with the R-(−)-synephrine (l-enantiomer) predominantly found in the immature fruits, rinds and leaves of Citrus aurantium whereas the S-(+)-enantiomer (d-enantiomer) is found only in small quantities in ethanolic extracts of the fruit. 8 The two enantiomers have been reported to a percentage ratio of 92:8 (R-synephrine: S-synephrine). 8,9 Animal studies have suggested that the R-(−)-enantiomer is the more potent agonist on vascular α-, β 1 -and β 2 -adrenoceptors, 10 while S-(+)-synephrine has been suggested to block noradrenaline reuptake, 11 which may elevate blood pressure and heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…8 The two enantiomers have been reported to a percentage ratio of 92:8 (R-synephrine: S-synephrine). 8,9 Animal studies have suggested that the R-(−)-enantiomer is the more potent agonist on vascular α-, β 1 -and β 2 -adrenoceptors, 10 while S-(+)-synephrine has been suggested to block noradrenaline reuptake, 11 which may elevate blood pressure and heart rate. There is a lack of human studies that investigate the stimulatory or sport performance effects synephrine enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…Various isomeric forms of synephrine are reported in the literature, but there is now a consensus that p ‐synephrine is the only form present in bitter orange 12 . It was also reported that the ( R )‐ isomeric form is the primary form naturally present and any ( S )‐ isomers were the result of racemization induced by heat 13 …”
Section: Introductionmentioning
confidence: 99%